1983
DOI: 10.1007/bf00395394
|View full text |Cite
|
Sign up to set email alerts
|

Phase-II clinical trial of 4′-epi-doxorubicin in metastatic solid tumors

Abstract: 4'-Epi-doxorubicin, one of the analogs of doxorubicin, was shown in experimental animal tumor models to have a wide spectrum of antitumor activity. In comparison, its toxic side effects were less prominent than those of doxorubicin. Results of the first phase-I and II clinical trials in human tumors have confirmed experimental data. The aim of our study was to carry out a broad phase-II clinical trial mainly in various types of primarily chemoresistant solid tumors to obtain further information on the antitumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

1983
1983
1990
1990

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 5 publications
0
6
0
2
Order By: Relevance
“…Epirubicin has been studied in phase I1 trials as single agent (199)(200)(201). The doses used have been between 75-100mg/m2 every 3 weeks.…”
Section: Gastric Cancermentioning
confidence: 99%
“…Epirubicin has been studied in phase I1 trials as single agent (199)(200)(201). The doses used have been between 75-100mg/m2 every 3 weeks.…”
Section: Gastric Cancermentioning
confidence: 99%
“…These data suggest that 4-epi-DX could be an active agent, but only in rectal and sigmoid cancer. Our personal observation sup ported this statement [12].…”
Section: -Epi-doxorubicin (4-epi-dx)mentioning
confidence: 75%
“…4'-Epi-DX has been tested as a single drug mostly in previously treated patients with response rates ranging from 0-25% (5,6). In some studies activity was reported as confined to rectosigmoid carcinoma (7)(8)(9), and recent reviews of the literature also showed a more pronounced activity in rectosigmoid carcinoma than in colon carcinoma (4,10). Only Falkson et al (6) have reported a significant response rate in colon carcinoma (7 out of 26 patients).…”
Section: Discussionmentioning
confidence: 99%